Making Sense of the Molly Maguires. - Kenny, Kevin (Oxford University Press, 1998)
A group of 20 Irish immigrants, suspected of comprising a secret terrorist organization called the "Molly Maguires", were executed in Pennsylvania in the 1870s for the murder of 16 men. This work offers a new interpretation of their dramatic story, tracing the origins of the group.